Social protection and children: a synthesis of evidence from Young Lives longitudinal research in Ethiopia, India and Peru - Porter, C (Young Lives, 2010)
This paper sets out the key findings from Young Lives research into the ways that major social protection policies are impacting on children, their families and communities in Ethiopia, India and Peru. Most research and policy debate focuses on effects of social protection on households, with children assumed to be passive beneficiaries of programmes to reduce vulnerability. Here we concentrate on children. Young Lives research finds that social protection schemes have both intended and unintended consequences for children, mostly positive but highlighting areas of concern that should be prioritised in programme design. For example, in Latin America, social protection has strongly moved in the direction of conditional cash transfers (CCTs) and the conditions attached to receipt of benefits are often directly aimed at child ‘welfare’, for example school attendance or visits to the health clinic. However, insights from qualitative analysis and child perspectives need to also enter into programme design. Social protection, commonly understood as government-led schemes that either mitigate risk or reduce vulnerability and/or chronic poverty, has moved up the policy and research agenda in recent years with cash transfers now present in 45 countries, covering 110 million families in the global south (Hanlon et al. 2010). In this paper, we explore three important social protection schemes in Ethiopia, India and Peru. While operating in quite different contexts, all three represent formal national schemes being fairly rapidly expanded, and all contain elements of `conditionality’ that affect children’s lives. In Ethiopia and India, this is a work requirement, and in Peru, there are conditionalities on beneficiaries that involve visiting health centres and school attendance. From Young Lives qualitative and quantitative analysis of social protection policies in these countries we find: Evidence of the public works scheme in India acting as a cushion, and possibly providing insurance affects: In Ethiopia, we find that schooling outcomes are improved by certain components of the Productive Safety Net Programme, though there are different impacts on boys and girls. In Peru there is evidence that conditional cash transfers are mainly reaching the intended beneficiaries. However Young Lives research also uncovers some of the unintended consequences of social protection for children: While children in Peru are attending school there are concerns that these increased demands on schools (through increases in class size) had not been adequately matched by investment. There is also evidence that programme placement has raised some tensions in the community – views that have been expressed by children and their communities in Young Lives sites. In Ethiopia and India, there is some evidence that public works schemes increase the work demands on children, either directly or through children substituting for adults in the household who are involved in the programmes. These findings must also be considered along with other evidence from qualitative work that documents how children are contributing to the household economy and managing risks themselves and with their families, and limited evidence on the extent to which increased work impacts on children’s schooling. Overall, child-focused research on social protection can provide important insights to make social protection more inclusive of children’s needs. This can improve programme design to make better use of scarce resources, and invest in the future of children in very poor communities. From these findings we draw a small number of key conclusions relevant to those seeking to ensure policymakers give close consideration to children’s needs and are increasingly child sensitive.